(untitled) (Research, Society and Development, 2023)
The present study aims to present how class II malocclusion is treated through orthognat ic surgery. The treatment of facial deformities requires the combination of orthodontic and orthognathic procedures, in addition to a multidisciplinary team. Class II patients are considered a more complete challenge, as compared to other class types, skeletal recurrence is considered the most common complication of orthognathic surgery. Through a bibliographic study, the understanding was built that orthognathic surgery seeks to normalize the patient’s dentofacial morphology, in order to leave the face in a normal shape. It aims to correct congenital or acquired problems that cause disharmony between the maxillary bones and mandible, promoting balance of function (chewing, breathing, speech, swallowing, occlusion) and facial harmony.